(untitled) (ENTHYMEMA, 2012)
We offer here the first Italian translation from the Russian of the initial part of a study dedicated to the word Pravda, to its complex semantic range, and to the history of this concept in its uses, effects, and multiple and interdependent meanings: philosophical, theological, juridical, and political. The study is contextualised in the frame of the experience of the Vocabulaire Européen des philosophies. Dictionnaires des intradui-sibles, of which Pravda represent an exemplar term.